Design and Computer Analysis of a Road Load Detection Machine - Li, Shuo; Zhao, Yan; Hwang, Don-Ha (Bright Publisher, 2022)
In this paper, an experimental device is designed for measuring vehicle dynamic load,the structure and stress of the equipment are analyzed by computer technology. The device design mainly includes vehicle, road surface, vehicle transmission, and control [1]. The vehicle is designed based on a 2-DOF vehicle model, the road is designed based on the Pasternak foundation model, and the control mainly uses a single-chip microcomputer. The dynamic response of vehicles to the road at different speeds is analyzed through the experiment.